Hydroids and hydromedusae of Southern Chesapeake Bay. - Calder, Dale R. (Charlottesville, Va. Virgina Institute of Marine Science, 1971)
Virginia Institute of Marine Science Special Papers in Marine Science; No. 1
Keywords: Hydromedusae--Southern Chesapeake Bay; Hydroids